An extremely rare case of 45X0/46Xi (Xq) Turner mosaic co-existing with schizophreniform disorder, a multidisciplinary management challenge: a case report and literature review - Ramu, Sivalakshmi; Singh, Nilanchali; Singh, Shalini; Meena, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Turner syndrome has various presentations such as short stature, webbed neck, amenorrhea, cubitus valgus, renal anomalies, cardiac defects, etc. Still, the concurrent psychiatric concerns with Turner syndrome are not well-established in the literature. Although most patients with Turner syndrome do not have any mental disorder, a significant proportion of patients with Turner mosaic develop schizophrenia and affective disorders. Very few sporadic cases have been reported in the literature that support the association of the Turner mosaic with schizophrenia and affective disorders worldwide. In this case report we will be discussing an 18-year-old who was identified as the 45X0 / 46Xi (Xq) Turner Mosaic by karyotyping. During her follow-up visits, she was diagnosed with a schizophreniform disorder. Individuals who have both these comorbid conditions are infrequent in this case. A multidisciplinary approach to management consisting of antipsychotics, supportive psychotherapy, and endocrine replacement therapy was initiated for our patient and she responded well on follow-up visits. Our case report adds a potential clue that emphasizes the association of Turner mosaic with the development of schizophrenia. It highlights the importance of early diagnosis of the syndrome and understanding its association with schizophreniform disorder, which should warrant the clinician’s early psychotherapy specified toward the psychological as well as the emotional aspects which might play a major role in preventing severe psychiatric complications in these patients. A literature review on this topic is also presented.